The juvenilization of American Christianity - Bergler, Thomas E., 1964- (Grand Rapids, Mich. : William B. Eerdmans Pub. Co., 2012)
Thomas Bergler traces the way in which, over seventy-five years, youth ministries have breathed new vitality into four major American church traditions -- African American, Evangelical, Mainline Protestant, and Roman Catholic. Bergler shows too how this "juvenilization" of churches has led to widespread spiritual immaturity, consumerism, and self-centeredness, popularizing a feel-good faith with neither intergenerational community nor theological literacy. Bergler's critique further offers constructive suggestions for taming juvenilization. --from publisher description
Introduction: we're all adolescents now -- Youth, Christianity, and the crisis of civilization -- Misreading the signs of the times: from political youth to trivial teenagers -- Social prophets or silent generation?: the failed juvenilization of liberal Protestantism -- The Black church and the juvenilization of Christian political activism -- Why everyone wanted to get out of the Catholic ghetto -- How to have fun, be popular, and save the world at the same time -- Youth, Christianity, and the 1960s apocalypse -- The triumph and taming of juvenilization.
Includes bibliographical references (p. 230-266) and index.
Keywords: Christianity -- United States -- 20th century; Christianity -- United States -- 21st century; Christianity and culture -- United States